(untitled) - RoAne, Susan (Hoboken, N.J., 2004)
The book includes making small talk; dropping names; eavesdropping and listening; straying from their chosen paths; and saying yes when they want to say no. Each chapter shares numerous stories of people turning serendipity (such as chance encounters) into success by utilizing at least one of these traits. "When we are open and pay attention to signs, signals, situations, and people, we are building our own internal serendipity generators," RoAne writes. However, aside from the inspiring examples, there's not enough specific "how-to" to help readers apply RoAne's advice to their own situations. While she puts a nice spin on basic networking principles, this somewhat repetitive book doesn't add much to the Chinese tenet "luck is when preparation meets opportunity.
Keywords: Success in business,Social networks,Serendipity,Thành công trong kinh doanh,Mạng lưới xã hội,Cầu may